Application of bipolar electrochemistry to assess the corrosion resistance of solution annealed lean duplex stainless steel - Yiqi Zhou; Sultan Mahmood; Dirk Lars Engelberg (Materials & Design, 2023)
The corrosion performance of type 2101 lean duplex stainless steel (LDSS) after different solution annealing heat treatments is investigated. The austenite to ferrite phase ratios and morphologies are correlated to their localised corrosion responses, with the application of bipolar electrochemistry providing access to pit nucleation and growth kinetics. The propagation of pitting corrosion via selective dissolution of the ferrite phase is observed, pointing towards a direct effect of ferrite morphology on pit shape. The corrosion behaviour of solution heat treatments are compared and ranked, providing information for improving and optimising the corrosion resistance of LDSS 2101 microstructures.